Medium-Run Impacts of Management Training in Garment Clusters - Higuchi, Yuki; Mhede, Edwin Paul; Nam, Vu Hoang; Sonobe, Tetsushi (Published by Oxford University Press on behalf of the World Bank, 2021)
This paper investigates the impact of management training programs on garment clusters in Vietnam and Tanzania. The study found that in the medium run firms showed improvement once they had identified useful practices and adapted them to their operations. Although it takes a few years to experience a significant impact on incomes, management training can increase not just management scores but also incomes or value added.